Health awareness and health culture among a sample of mothers aged (20 – 43 year) lived in urban and rural zones in Baghdad (Journal of the College of Education for Women, 2019)
The study aimed to identify the level of health awareness and health education among mothers zones, urban and rural areas as well as to identify the differences between them and to achieve this study was conducted on a sample of (121) or been Akhittarhn randomly, aged (20 - 43 years) and applied them to a questionnaire to measure the health awareness, which formed from a group of paragraphs, and after the collection of data was treated using the statistical software (SAS), where research showed many of the results are:1/ Reached the age group ranging between (20-30 years), the highest rate for the present, where was (40.51%), while in the countryside matched by age group (31-40 years old) in terms of (54.76%)./ It turns out that the percentage of mothers who read health guidelines affixed (posters) in health centers in rural areas is higher than in urban areas where the percentage ratio (38.10%) in the countryside and are offset (26.58%) in urban areas.3 / turns out that mothers who read health guidelines in the health centers are the holders of primary and intermediate certificate in urban areas while in rural areas are of primary school graduates4 / It turns out that the percentage (67.9%) of the Ganh study in urban areas are watching a Asahahbinma outreach programs in the countryside percentage (11.90%).5 / shows that the percentage (24.5%) of the studied sample in urban areas are with secondary education who are watching a health awareness programs while the increase in rural areas (7.14%) are of medium degree holders.6 / percentage of mothers who are keen to review the health centers in urban areas is higher than in the countryside where the percentage of (50.63%) and (50.00%), respectively.7 / It turns out that mothers in urban areas turn to see a doctor when feeling unwell while mothers in the countryside resort to charge pharmacist consultation.8 / shows that mothers who turn to see the doctor in urban areas are of the certificate junior campaign and its percentage (35.29%)9 / turns out that mothers who turn to see the doctor in the countryside are holders of certificate of primary and percentage (50.00%), while the percentage (76.47%) are of primary school graduates have recourse to the pharmacist in charge.